First record of Branchipodopsis affinis Sars, 1901 (Crustacea: Anostraca) in Iran (Bazargan, West Azerbaijan): Ecology, Morphology and Genetics - Kangarloei, Behrooz Atashbar; Roohi, Maryam (Zootaxa, 2021)
We report the first record of Branchipodopsis affinis Sars, 1901 (Branchiopoda, Anostraca) from Iran. The specimens were collected in small temporary pools in the Bazargan area located in West Azerbaijan province, in spring 2015. Details on the biogeography, ecology and morphology of this species are provided. The DNA sequence data (COI) for this species is reported for the first time, which can be used in the identification of species on molecular terms and generation of information regarding the evolutionary relationship of the species in future. Also, the new finding is an important contribution to the knowledge of the anostracan fauna from Iran.